Reform! - (:unkn) unknown (Ruby Press, 2015)
The fourth volume in the series Essays on the Political Economy of Urban Form argues that sometimes the most effective path to meaningful change is to work within existing institutions and slowly, surely, push for it. This is all the more relevant for architecture, which by definition is entrenched in larger social, economic, and political contexts. Architecture s captivity to external interests should not be seen as a weakness, but rather as a unique opportunity to change things up. The book collects four essays debating reform in topics as diverse as urban planning policy in Mumbai, troubling city fabrics in Detroit, the failings of municipal housing in Diyarbakir (Turkey), and building processes in Tirana (Albania). With contributions by Rahul Mehrotra (Harvard University), Jason Young (University of Tennessee, Knoxville), Sarah Nichols and Martino Tattara (ETH Zurich), Freek Persyn (51N4E).
Keywords: Stadtplanung; Stadtgestalt; Städtebau; Planungspolitik; Institution; Architektur; Urbanität; Stadtstruktur; Wohnungsbau; Beispielsammlung; Stadtgrundriss; Transformation; Politischer Wandel